LAparoscopic Versus Abdominal hysterectomy (LAVA): protocol of a randomised controlled trial - Laura Jones; Peter Brocklehurst; Rebecca Woolley; Paul Smith; Lee Middleton; Tracy Roberts; Ertan Saridogan; Lina Antoun; T Justin Clark; William McKinnon; Kevin Cooper; Sheriden Bevan; et al. (BMJ Open, 2023)
Introduction There is uncertainty about the advantages and disadvantages of laparoscopic hysterectomy compared with abdominal hysterectomy, particularly the relative rate of complications of the two procedures. While uptake of laparoscopic hysterectomy has been slow, the situation is changing with greater familiarity, better training, better equipment and increased proficiency in the technique. Thus, a large, robust, multicentre randomised controlled trial (RCT) is needed to compare contemporary laparoscopic hysterectomy with abdominal hysterectomy to determine the safest and most cost-effective technique.Methods and analysis A parallel, open, non-inferiority, multicentre, randomised controlled, expertise-based surgery trial with integrated health economic evaluation and an internal pilot with an embedded qualitative process evaluation. A within trial-based economic evaluation will explore the cost-effectiveness of laparoscopic hysterectomy compared with open abdominal hysterectomy. We will aim to recruit 3250 women requiring a hysterectomy for a benign gynaecological condition and who were suitable for either laparoscopic or open techniques. The primary outcome is major complications up to six completed weeks postsurgery and the key secondary outcome is time from surgery to resumption of usual activities using the personalised Patient-Reported Outcomes Measurement Information System Physical Function questionnaire. The principal outcome for the economic evaluation is to be cost per QALY at 12 months’ postsurgery. A secondary analysis is to be undertaken to generate costs per major surgical complication avoided and costs per return to normal activities.Ethics and dissemination The study was approved by the West Midlands-Edgbaston Research Ethics Committee, 18 February 2021 (Ethics ref: 21/WM/0019). REC approval for the protocol version 2.0 dated 2 February 2021 was issued on 18 February 2021.We will present the findings in national and international conferences. We will also aim to publish the findings in high impact peer-reviewed journals. We will disseminate the completed paper to the Department of Health, the Scientific Advisory Committees of the RCOG, the Royal College of Nurses (RCN) and the BSGE.Trial registration number ISRCTN14566195.